Sociodemographic profile of depression in the elderly in brasil: integrative review - Ilda Fernandes; Fabrícia Neves; Patrícia Guimarães; Karla Maria Rolim; Firmina Hermelinda Albuquerque; Luisa Andrade; Rejane Milliones (Instituto Politécnico de Viseu, 2020)
Introduction: The prevalence of clinically significant depressive symptoms in the elderly is high. Therefore, it is essential that health professionals know the dominant profile of this nosological entity. Objectives: To identify in the literature, the sociodemographic profile of elderly people affected by depression between 2002 and 2016. Methods: Integrative literature review, carried out in the Latin American and Caribbean Health Sciences (LILACS) and Scientific Electronic Library Online (SciELO) databases, using the descriptors: depression, the elderly and geriatrics. Results: The prevalence of depressive illness significantly affects females (90%), aged over 60. The socio-demographic profile identifies white elderly, single, Catholic, illiterate, of medium economic level, with a family history. The use of illicit and licit drugs and a high rate of cognitive deficit are also prevalent characteristics in the profile of an elderly person with depression. Conclusions: Over the past few years, the elderly population has been showing an increase in mental illnesses, including depression. This, therefore, deserves more qualified and humanized attention by the health team, with the aim of reducing the rates of mental disorders in the elderly.